Analisis Pendidikan Islam: Antara Pengembangan Kreativitas dan Doktrinasi Ideologi Keagamaan - Sepma Pulthinka Nur Hanip (Universitas Islam Negeri (UIN) Mataram, 2021)
In recent decades, Islamic educational institutions have been widely established in Indonesia. More importantly, these Islamic educational institutions have affiliations with Islamic organizations such as Muhammadiyah, Nahdlatul Ulama, Nahdlatul Wathan in Lombok and even transnational Islamic organizations such as salafis. This study is focused on searching and analyzing to find a balance between the development of creativity and the ideological doctrine that exists in the body of Islamic education affiliated with Islamic organizations. The research method used is library research or literature study with a philosophical approach. This research proves that: (1) creativity finds its form in the ijtihad space as an effort to produce new perspectives; (2) embedded religious ideology contained in the curriculum taught in Aswaja and NU's Education, Al-Islam and Kemuhammadiyahan, NW's, and salafi management; (3) Islamic education is not only limited to the doctrination of religious idoelogi alone.